The hidden side of plant invasions: the role of genome size - Suda, Jan; Meyerson, Laura A; Leitch, Ilia J; Pyšek, Petr (The New phytologist, 2015)
The ecological role of genome size in plant biology, biogeography, and morphology has garnered increasing attention as the methods and technology associated with measuring cytological characteristics have become more reliable and accessible. However, how plant genome size influences plant invasions and at what stage in the invasion this influence occurs have been little explored. Several large-scale analyses of published data have yielded valuable interspecific comparisons, but experimental studies that manipulate environmental factors are needed, particularly below the species level, to fully understand the role that genome size plays in plant invasion. In this review, we summarize the available knowledge, discuss the integration of genome size data into invasion research, and suggest how it can be applied to detect and manage invasive species. We also explore how global climate change could exert selective pressures on plant populations with varying genome sizes, thereby increasing the distribution range and invasiveness of some populations while decreasing others. Finally, we outline avenues for future research, including considerations of large-scale studies of intraspecific variation in genome size of invasive populations, testing the interaction of genome size with other factors in macroecological analyses of invasions, as well as the role this trait may play in plant-enemy interactions.
Keywords: délka genomu; klimatické změny; rostliny; Climate Change; Ecosystem; flow cytometry; C-value; genetická variace; zavlečené druhy; Plants; ekosystém; plant traits; Phragmites; Introduced Species; Genome Size; global climate change; polyploidy; naturalization; Cx-value; genom rostlinný; Genome, Plant; Genetic Variation